Emotions and Needs in the School Space of 10-year-Old Children - Psychological and Linguistic Analysis of Personal Narratives in the Light of the GLOBAL TALES Protocol - Agnieszka Dłużniewska; Kamil Kuracki (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: Children's personal narratives are an important source of knowledge about experiences generating both positive and negative emotions, as well as about revealed psychological needs. The Global Tales protocol used in the study allows e.g. to identify those that directly relate to functioning in the school environment. Research Aim: The aim of the research was to identify significant situations in the narratives of 10-year-old children in response to the six prompts of the Global Tales protocol, and to identify linguistic means of expressing emotions and psychological needs in the context of telling about experiences related to school functioning of the surveyed children. Method: Twenty-five 10-year-old children without diagnosed developmental dysfunctions took part in the study conducted using the Global Tales protocol. After the children's responses were transcribed, a qualitative and quantitative analysis was carried out to identify significant situations generating positive and negative emotions and to recognize the linguistic means of expressing emotions and psychological needs in children's narratives. Results: The study made it possible to identify what significant experiences revealed in children's narratives generate positive and negative emotions, what part of them relate to the school environment and functioning as a student, how children construct narratives about situations that are significant in the linguistic layer, including in the context of the use of universal units of natural language, and what psychological needs are revealed in children's statements about experiences related to events related to the school environment. Conclusions: The research will complete an important area of knowledge about children's use of language to express emotions and needs related to significant situations in school functioning. The Global Tales protocol can be used as a tool for the psychological-linguistic analysis of children's narratives in late school age.